Breastfeeding and Beyond - Sansone, Antonella (International Journal of Child Health and Nutrition, 2013)
This paper draws on the last chapter of my forthcoming book Window to The Womb. How Prenatal Life Shapes a Baby’s Development, which is an unprecedented dialogue between scientific research and maternal subjective experience. It highly acknowledges the supreme importance of the woman’s healthy nutrition and emotional nurturing to create an optimal womb environment and transmit a positive attitude to nutrition – and to life in general – to the child. In particular, breastfeeding may reinforce this attitude and allow for the baby’s smooth transition from the flavours of the amniotic fluid, introduced by the mother’s healthy food, to those present in the breast milk, which the baby recognises as familiar. Therefore, the benefits of breastfeeding are not limited to its nutrients but extend to the reassuring experience of continuity from the womb life, building the foundations of the baby’s emotional security.